2018
DOI: 10.1016/j.jid.2017.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Repigmentation of Human Vitiligo Skin by NBUVB Is Controlled by Transcription of GLI1 and Activation of the β-Catenin Pathway in the Hair Follicle Bulge Stem Cells

Abstract: Vitiligo repigmentation is a complex process in which the melanocyte-depleted interfollicular epidermis is repopulated by melanocyte precursors from hair follicle bulge that proliferate, migrate, and differentiate into mature melanocytes on their way to the epidermis. The strongest stimulus for vitiligo repigmentation is narrow-band UVB (NBUVB), but how the hair follicle melanocyte precursors are activated by UV light has not been extensively studied. To better understand this process, we developed an applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 51 publications
3
39
0
Order By: Relevance
“…A recent study by Zhang et al (2019) reported that HMGB1 could be released from melanocytes exposed to UVB and promote the activation of ERK pathway in melanocytes in an autocrine way, which is consistent with the paracrine effects of HMGB1 on keratinocytes observed in our study. Notably, UVB phototherapy is a commonly used strategy for treating vitiligo by activating melanocyte stem cells and suppressing the function of autoreactive T cells (Bulat et al, 2011;Goldstein et al, 2018). However, the therapeutic effect of UVB phototherapy is limited, given that a considerable portion of patients with vitiligo is not responsive (Silpa-Archa et al, 2018), which may be due to the proinflammatory effects of UVB-induced HMGB1 on keratinocytes, according to our findings.…”
Section: Discussionsupporting
confidence: 63%
“…A recent study by Zhang et al (2019) reported that HMGB1 could be released from melanocytes exposed to UVB and promote the activation of ERK pathway in melanocytes in an autocrine way, which is consistent with the paracrine effects of HMGB1 on keratinocytes observed in our study. Notably, UVB phototherapy is a commonly used strategy for treating vitiligo by activating melanocyte stem cells and suppressing the function of autoreactive T cells (Bulat et al, 2011;Goldstein et al, 2018). However, the therapeutic effect of UVB phototherapy is limited, given that a considerable portion of patients with vitiligo is not responsive (Silpa-Archa et al, 2018), which may be due to the proinflammatory effects of UVB-induced HMGB1 on keratinocytes, according to our findings.…”
Section: Discussionsupporting
confidence: 63%
“…Among the various pitfalls of NBUVB phototherapy as the main option for vitiligo treatment, one is the refractoriness and less responsiveness of repigmentation over time 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, UV may directly affect the hair follicle cycling. A recent study showed that UVB light‐induced repigmentation of vitiligo patches by activating the β‐catenin pathway of hair‐follicle bulge stem cells 26 . As Wnt/β‐catenin signaling in dermal papilla cells is the canonical pathway inducing anagen phase and stimulating hair growth, 27,28 activation of the β‐catenin pathway by UVB light may stimulate hair regrowth of AA lesions.…”
Section: Discussionmentioning
confidence: 99%